Biodiesel Production from Rambutan Seed Waste by Supercritical Ethanol: Economic Analysis - Wirasinee Supang; Kamonthip Nilmat; Winatta Sakdasri; Kassama Utthachat; Somkiat Ngamprasertsith; Rueangwit Sawangkaew (Chemical Engineering Transactions, 2025)
The production capacity of rambutan (Nephelium lappaceum Linn.) in Thailand is approximately 0.3–0.4 million tons per year, and an average of 1,900 tons of rambutan seed is left as seed waste. This work pre-extracted rambutan seed oil using a single screw press machine to serve as feedstock for biodiesel production. However, the rambutan seed had a high lipid content of ~40%; the screw press machine was capable of extracting only 6–10% of the rambutan seed oil; in other words, ~24% of the residual oil remains in the seed cake. An ethanolic extraction was performed to recover the remaining lipids in the pressed seed cake. This work also aimed to use ethanol as a reactant for biodiesel production in supercritical conditions without removing the extracting ethanol. Ethanolic extraction and supercritical ethanol transesterification were collectively called the EE-SET process. The fatty acid ethyl esters (FAEE) content in the resultant biodiesel ranged from 40–60% because rambutan seed oil contained ~50% oleic (C18:1) and ~40% arachidic (C20:0) acids, which have higher molecular weights than common plant oil. Next, the experimental conditions were simulated in Aspen Plus V.12 software to estimate the mass and energy balances in the biodiesel production process. The results from computer simulations were applied to an economic analysis to assess the feasibility of the EE-SET process. Because the unique fatty acid profile of rambutan seed oil generated a lower FAEE content and consumed a large amount of energy for distillation, the process's complexity reduced the EE-SET process's profitability.